PERANCANGAN TATA LETAK MESIN PRODUKSI UNTUK MENGURANGI BIAYA MATERIAL HANDLING PADA INDUSTRI LOGAM - Anita Oktaviana Trisna Devi; Bayu Seto (JURNAL GAUNG INFORMATIKA, 2017)
Manufacturing industry is always required to carry out efficiency and effectiveness in the production system. One strategy can be done to achieve is through setting the layout of the facility. By structurizing the layout of good facilities, companies can reduce production costs without reducing the quality of the products produced. One of the companies that designs the facilities layout to increase the efficiency and effectiveness of the production system is PT. AGNA INSPIRE, manufacturer of slider frames in the Banjarsari area, Surakarta. The company plans to replace machinery and move the factory to another location. The arrangement of the machines carried out in the previous factory only considered empty space, regardless of the order of the production process. In fact, the company's production is made to stock and the arrangement of the machines should follow the order of the process. Therefore, it is necessary to design the layout of operating machinery facilities by considering thesequence of processes to minimize distance and material handling costs. The method used in determining the layout is the blockplan method. Based on the results of data processing, the proposed layout design was obtained with Material Handling Cost (OMH) of Rp. 651,000. This value is more efficient than OMH in the previous layout of Rp. 1,036,000, -